Effect of collagen-chitosan hydrogel formula combined with platelet-rich plasma (A study of ph, viscocity, and swelling test) - Tutut Prabantari Anindyajati; Sri Pramestri Lastianny; Flandiana Yogianti; Kwartarini Murdiastuti (Faculty of Dentistry, Universitas Gadjah Mada, 2020)
Platelet-rich plasma (PRP) contains growth factors that speed up a healing process. The liquid form of PRP is difficult to be applied, so it needs material as a carrier of collagen. Collagen can be used as carrier materials and capable to activate growth factors and increase the concentration of the PRP to become a gel. Collagen often losses its shape and size due to degradation when exposed to body fluids. In the selection of materials, collagen can synthesize with chitosan. Collagen-chitosan hydrogel has potential as scaffold. Many formulations for proper hydrogel applied in the oral cavity need to pay more attention to several conditions, such as a neutral pH, high viscosity and ideal swelling. The aims of this study was to examine the influence of various formulations of collagenchitosan hydrogel PRPagainst pH, viscosity, and swelling. The study samples consisted of 25 collagen-chitosanhydrogel formulations. The samples were divided into five groups: 100/0; 75/25; 50/50; 25/75; 0/100. The first stage of the test was pH, viscosity and swelling measurement of the collagen-chitosan hydrogel to determine which ones matched the criteria. Collagen-chitosan hydrogel formulations were added with PRP with a ratio of 1:1. The second stage was to measure the pH, viscosity, and swelling measurement to see the results of the physical parameters of the hydrogel after mixed with PRP. The observation data were analyzed by t-test for pH and viscosity, while twoway ANOVA and post hoc LSD for swelling test. The results showed that collagen-chitosan hydrogel formulations of 25/75 and 0/100 met the criteria of pH, viscosity, and swelling. The pH of both groups showed no significant difference (p>0.05), but the viscosity and swelling variables showed significant difference (p<0.05). To conclude, collagen-chitosan hydrogel formulations mixed with PRP had no effect on pH, but had an effect on viscosity and swelling test. The collagen-chitosan hydrogel formulations mixed with PRP which matched the criteria were 25/75 and 0/100.